Higher risk of adverse cardiovascular outcomes in women with type 2 diabetes mellitus: an umbrella review of systematic reviews. (25th January 2023) - Chong, B; Yaow, C; Chin, Y H; Ng, C H; Goh, R; Kong, G; Muthiah, M; Sukmawati, I; Lukito, A A; Chan, M Y; Khoo, C M; Mehta, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Previous studies have shown that females with type 2 diabetes mellitus (T2DM) may have an excess mortality risk compared to males. Furthermore, other studies have reported sex differences in managing cardiovascular risk factors, such as controlling hypertension and hypercholesterolemia. Purpose: With the growing evidence from systematic reviews examining the sex differences in cardiovascular outcomes for patients with T2DM, an umbrella review is an essential next step to synthesising and assessing the strength of the available evidence. Methods: Medline and Embase were searched from inception till 7th August 2022 for systematic reviews and meta-analyses studying the effects of sex on cardiovascular outcomes in T2DM patients. Results from reviews were synthesised with a narrative synthesis, with a tabular presentation of findings and forest plots for reviews that performed a meta-analysis. AMSTAR 2 tool was used to assess the methodological quality of included reviews, while the GRADE assessment was used to assess the quality of evidence for outcomes. Results: A total of 28 studies evaluating sex differences in cardiovascular outcomes were included. Females with T2DM had a higher risk of developing coronary heart disease (CHD; RRR 1.52, 95%CI 1.32–1.76, p<0.001), acute coronary syndrome (ACS; RRR 1.38, 95%CI 1.25–1.52, p<0.001), and heart failure (RRR 1.09, 95%CI 1.05–1.13, p<0.001) than males. In terms of mortality outcomes, females had a higher risk of all-cause mortality (RRR 1.13, 95%CI 1.07–1.19, p<0.001), cardiac mortality (RRR 1.49, 95%CI 1.11–2.00, p=0.009) and CHD mortality (RRR 1.44, 95%CI 1.20–1.73, p<0.001) as compared to males. In patients undergoing percutaneous coronary intervention, females reported higher odds of MACE (OR 1.49, 95%CI 1.07–2.07, p=0.020) and all-cause mortality (OR 1.71, 95%CI 1.46–2.00, p<0.001) compared to males. Females in Asia (RRR 1.12, 95%CI 1.03–1.21, p=0.006) and North America (RRR 1.10, 95%CI 1.08–1.12, p<0.001) were at increased risk of all-cause mortality while females in Western countries had an increased risk for cardiac death (RRR 1.84, 95%CI 1.45–2.32, p<0.001) compared to males. Six reviews were rated as high in quality; eight reviews were rated as moderate, and fourteen reviews were rated as low in quality. Regarding the quality of outcomes, all outcomes in non-interventional studies had a moderate quality of evidence, while all outcomes in interventional studies achieved a high quality of evidence. Conclusions: This umbrella review evaluated the quality of meta-analyses and demonstrated that females with T2DM have a higher risk of cardiovascular outcomes than their male counterparts. Future studies examining the sex differences in outcomes should attempt to address the heterogeneity and epidemiological factors for a better quality of evidence. Policymakers should consider sex-specific differences in implementing effective tailored strategies to tackle T2DM.